Guide to America's federal jobs a complete directory of U.S. government career opportunities - Taylor, Karol; Ruck, Janet M.; Safari eBooks (Indianapolis, IN : JIST Works, 2009)
This resource helps you navigate the federal hiring process--including the official employment Web site and lengthy job announcements. Discover the types of jobs available, how to find openings that fit your background, key terminology, how to make your application stand out, and more.--From publisher's description.
Description based on print version record.
Includes list of web sites (p. 379-383).
Includes bibliographical references and index.
Keywords: Civil service positions -- United States -- Directories; Electronic books